Coastal curios? An analysis of ex situ beach finds for mapping new Palaeolithic sites at Happisburgh, UK. (11th February 2021) - Bynoe, Rachel; Ashton, Nick M.; Grimmer, Tim; Hoare, Peter; Leonard, Joanne; Lewis, Simon G.; Nicholas, Darren; Parfitt, Simon
Abstract: Recent archaeological discoveries from exposures of the Cromer Forest‐bed Formation at Happisburgh, UK, have radically changed interpretations of the nature and timing of early hominin occupation of northern latitudes, but this in situ archaeology is only one part of the picture. Surface finds of Pleistocene mammalian remains have been found along this coastline for centuries, with stone tools adding to this record over the past 7 years. The ex situ nature of these finds, however, means they are often seen as limited in the information they can provide. This work contributes to a growing body of research from a range of landscape and environmental contexts that seeks to demonstrate the value and importance of these ex situ assemblages. Here the focus is on Palaeolithic flint artefacts and Pleistocene mammalian remains recovered by a group of local collectors through systematic, GPS‐recorded beach collection from 2013 to 2017, and their use in developing a methodology for working with ex situ Palaeolithic finds in coastal locations. The results demonstrate significant patterning that identifies unexplored exposures both onshore and offshore, considerably expanding the known extent of deposits and facilitating new insights into the wider archaeological landscape associated with the earliest occupation of northern Europe.